2016
DOI: 10.1038/srep20147
|View full text |Cite
|
Sign up to set email alerts
|

A physiological role of cyclic electron transport around photosystem I in sustaining photosynthesis under fluctuating light in rice

Abstract: Plants experience a highly variable light environment over the course of the day. To reveal the molecular mechanisms of their photosynthetic response to fluctuating light, we examined the role of two cyclic electron flows around photosystem I (CEF-PSI)—one depending on PROTON GRADIENT REGULATION 5 (PGR5) and one on NADH dehydrogenase-like complex (NDH)—in photosynthetic regulation under fluctuating light in rice (Oryza sativa L.). The impairment of PGR5-dependent CEF-PSI suppressed the photosynthetic response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
194
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(205 citation statements)
references
References 32 publications
10
194
1
Order By: Relevance
“…In line with recent studies (Ivanov et al, 2015;Yamori et al, 2016), F v /F m and F v '/F m ' measured as the PSII photochemical efficiency and the antenna efficiency, respectively, in tomato plants under HH were both inhibited in an identical manner to those in peas and rice (Figs. 3a and 3b), where F v is the variable fluorescence which yields in the dark state.…”
Section: Effects Of Dcmu and MV On Psii Activitysupporting
confidence: 70%
See 1 more Smart Citation
“…In line with recent studies (Ivanov et al, 2015;Yamori et al, 2016), F v /F m and F v '/F m ' measured as the PSII photochemical efficiency and the antenna efficiency, respectively, in tomato plants under HH were both inhibited in an identical manner to those in peas and rice (Figs. 3a and 3b), where F v is the variable fluorescence which yields in the dark state.…”
Section: Effects Of Dcmu and MV On Psii Activitysupporting
confidence: 70%
“…When photosynthetic organisms are exposed to all kinds of environmental stresses like high or low temperature, water or nutrient stress, and light intensity exceeds the leaf's ability to use it, this can lead to an imbalance between the capability for absorbing light energy and consuming this excess light energy through metabolic mechanisms, resulting in the generation of reactive oxygen species (ROS) which are injurious to photosystems (Chen et al, 2012;Yamori et al, 2016). Extensive research has shown that many sites in the photosynthetic membrane are susceptible to high temperature and high light intensity (HH), in particular photosystem II (PSII) (Pospisil, 2012;Deng et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with the role of CEF in the activation of 537 ATP production and qE (Munekage et al, 2004;Yamori et al, 2016) COP1-RNAi and RBOH1-RNAi plants were generated as described previously (Liu et al, Table S3). The PCR product was cloned into pFGC1008-HA …”
mentioning
confidence: 99%
“…The high light levels caused by the focusing effect of the epidermis and the fluctuating light conditions together can pose a significant stress for photosystems in different chloroplasts inside a leaf. In line with this, fluctuating light causes photoinhibition in both rice and Arabidopsis (Kono et al , 2014; Yamori et al , 2016). …”
Section: Discussionmentioning
confidence: 71%